Managerial Shareholding and Performance in LBOs: Evidence from the MENA Region - Abir Attahiri; Maroua Zineelabidine; Mohamed Makhroute (Economies, 2025)
This research explores the impact of ownership structure on the financial performance of Leveraged Buyout (LBO) transactions in the MENA region, a key emerging market region. Drawing on agency theory by Jensen & Meckling and the capital structure theory of Modigliani and Miller, the study investigates how different shareholder configurations, particularly managerial equity participation, influence LBO outcomes. Based on a sample of 233 transactions conducted between 2000 and 2023, the research adopts a quantitative methodology grounded in a hypothetico-deductive approach. The analysis focuses on the interactions between managerial ownership, leverage, target firm size, and operational performance. The findings support the agency theory premise that managerial ownership aligns interests and enhances performance, showing a positive relationship between managerial equity stakes and financial outcomes. Conversely, the effect of leverage, central to Modigliani and Miller’s propositions, proves more nuanced, reflecting the region’s unique financial constraints and market imperfections. Firm size, meanwhile, shows no direct correlation with performance improvement. These insights underscore the complex mechanisms behind LBO success in the MENA context and offer practical and theoretical implications, particularly regarding governance practices and institutional frameworks. The study also outlines avenues for future research, including a deeper examination of regional governance dynamics.